2008
DOI: 10.1200/jco.2007.13.5822
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Randomized Placebo Controlled Trial of Fulvestrant Compared With Exemestane After Prior Nonsteroidal Aromatase Inhibitor Therapy in Postmenopausal Women With Hormone Receptor–Positive, Advanced Breast Cancer: Results From EFECT

Abstract: Fulvestrant LD and exemestane are equally active and well-tolerated in a meaningful proportion of postmenopausal women with ABC who have experienced progression or recurrence during treatment with a nonsteroidal AI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
204
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 467 publications
(223 citation statements)
references
References 30 publications
11
204
1
7
Order By: Relevance
“…The apparent sensitivity of MCF7-LTED cells to further antiestrogenic treatment such as fulvestrant (Santen et al, 2001;Chan et al, 2002;Martin et al, 2003) substantiates this theory, leading to the proposal of clinical trials including these treatments and/or growth factor signaling inhibitors. However, these approaches have shown limited efficacy; in fact, fulvestrant only elicits a response in approximately 7% of ERa-positive tumors that regrow under AI therapy, although its clinical use is justified based on a clinical benefit rate of 32% (Chia et al, 2008). On the other hand, trials with combinations of AIs and growth factor signal inhibitors have not improved outcomes in most cases , except for recent results on novel combinations that are still under research (Baselga et al, 2009;Johnston et al, 2009).…”
Section: Effect Of 17be2 Through Eramentioning
confidence: 99%
“…The apparent sensitivity of MCF7-LTED cells to further antiestrogenic treatment such as fulvestrant (Santen et al, 2001;Chan et al, 2002;Martin et al, 2003) substantiates this theory, leading to the proposal of clinical trials including these treatments and/or growth factor signaling inhibitors. However, these approaches have shown limited efficacy; in fact, fulvestrant only elicits a response in approximately 7% of ERa-positive tumors that regrow under AI therapy, although its clinical use is justified based on a clinical benefit rate of 32% (Chia et al, 2008). On the other hand, trials with combinations of AIs and growth factor signal inhibitors have not improved outcomes in most cases , except for recent results on novel combinations that are still under research (Baselga et al, 2009;Johnston et al, 2009).…”
Section: Effect Of 17be2 Through Eramentioning
confidence: 99%
“…Recently, the overall analysis from the EFECT trial demonstrated that fulvestrant and exemestane have comparable efficacy and tolerability in postmenopausal women with advanced breast cancer following non-steroidal AI failure [12].…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study design and methodology of EFECT have been reported previously [12]. Briefly, EFECT (study code 9238IL/0048) is a randomised, double-blind, doubledummy, multicentre, Phase III trial comparing the efficacy and tolerability of fulvestrant versus exemestane in postmenopausal women with hormone receptor-positive, locally advanced or metastatic breast cancer.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations